From Theory to Practice: A Dynamic Systems Model for Enhanced Governance in Higher Education - Gunawan, Muhammad Ali; Maulida, Minati; Muhammad, Adib (JURNAL AL-TANZIM, 2024)
This study aims to analyze the governance of higher education institutions facing specific challenges, using a dynamic system model to gain a deeper understanding compared to traditional governance approaches. The approach used in this study is qualitative, with a case study design and purposive sampling technique to select participants. Data were collected through interviews, observations, and document analysis, which were then analyzed using thematic analysis. The study results indicate that effective governance relies on adaptive leadership, transparency in decision-making, and active stakeholder participation. This study contributes by developing a measurable framework to assess these governance elements and demonstrating how a dynamic system model can improve institutional performance. Practical implications of this study include the importance of aligning leadership practices with the specific needs of the institution, as well as the need to increase stakeholder engagement. Recommendations generated from this study are expected to be applied to other higher education institutions facing similar challenges to improve governance effectiveness and institutional performance.